The Gift Theology of Luther and Calvin - GAO, Zhe (Journal of Research for Christianity in China (JRCC), 2025)
This project seeks to elaborate the notion of Gift in Luther’s and Calvin’s theologies in the context of contemporary theological discussion of gift. For anyone who is interested in this topic, both Martin Luther and John Calvin are those they cannot ignore. The most signifi- cant character of the reformers’ theologies lies in their exclusive emphasis on the grace of God, which is exactly another name of God’s gift. With regard to this, this essay shows how the interpretation of gift in Luther and Calvin could be assimilated by contemporary theology of gift, while offering a critical reflection on their theory through a critical dialogue with cer- tain contemporary thinkers such as John Milbank and Jacques Derrida.